PENDAFTARAN HAK MILIK ATAS TANAH TERHADAP HARTA GONO – GINI YANG BELUM DILAKUKAN PEMBAGIAN - Johannes Parningotan; Abdul Mukmin (Yuriska: Jurnal Ilmiah Hukum, 2016)
Indonesia is a state of law as set forth in the 1945 Constitution and contained in article 1 paragraph (3) that, the state of Indonesia is a state of law, therefore Indonesia is a country of law. That is why the implementation of the state should be based on law, including provisions in the agrarian field. The provisions of the law in the agrarian field in the codification in Law No. 5 of 1960 About the Basic Regulation of Agrarian Principles (State Gazette Year 1960 Number 104, Additional State Gazette No. 2043), hereinafter abbreviated as BAL, but in certain cases how legal certainty in the land registry to assets marriages that have not performed the division as a result of a divorce that has been decided by the competent authority in this case the Religious Court or District Court.